Polytope Prediction for Dengue Vaccine Candidate Based on Conserved Envelope Glycoprotein of Four Serotypes of Dengue Virus and Its Antigenicity - Karimatul Himmah; Fitriyah Fitriyah; Tri Ardyati; Custer Deocaris; Nashi Widodo (Chemistry Department, The University of Brawijaya, 2016)
Dengue fever reported endemic in tropical and sub-tropical country. Dengue fever caused by dengue virus, has Envelope protein that often used for vaccine development to prevent the virus infection. Vaccine development to prevent four serotype dengue virus infection still unavailable. This study aims to design polytope from four conserved epitopes of dengue virus envelope glycoprotein to prevent infection of heterotypic dengue virus and predict its antigenic challenge by molecular docking. We investigate molecular modeling of polytope, immunoinformatics analysis of polytope, protein structure of antibodies, molecular docking and protein-protein docking assessment. The polytope categorized as a stabil protein with index 29.72, has molecular weight 6,139 kDa, has three exposed antigenic determinants region and has estimated half-life is: 3.5 hours (mammalian reticulocytes, in vitro),10 min (yeast, in vivo), and >10 hours (Escherichia coli, in vivo). The Polytope binds with four broadly neutralizing antibodies of B7, C8, A11, and C10 (bnAbs) which estimated that four bnAbs can recognize four serotypes of dengue virus. The designed polytope has prospect to produce in Escherichia coli and can be applied as vaccine of heterotypic dengue virus serotype. Polytope is potentially able to generate humoral and cellular immunity.